Efek Perceived Value terhadap Retentsi Pelanggan dengan Trust sebagai Media Variabel di Perusahaan X - Prasetyo Tejo, Meliyana (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2021)
This research was conducted to determine the effect of perceived value on trust, the purposes are to know the effect of perceived value on customer retention, to know the effect of trust on customer retention, to know the role of trust as mediator in the relationship between perceived value on customer retention in Company X family business which moved as distributor basic needs. Research data collection was distributed to 68 respondents of Company X B2B customer who regularly purchase on 2020. Analysis method for this research used Partial Least Square Structural Equation Modeling (SEM PLS) with smart PLS 3.0 program. The results of the analysis in this study are perceived value have a positive relationship and significant effect on trust; perceived value doesn’t have significant effect on customer retention in Company X; trust has a positive and significant effect on customer retention in Company X; Trust fully mediates perceived value to customer retention in Company X. Managerial implications based on the results are creating more services and educate customer about service offer compared with competitors, improving service with implementing computerize system to decrease error, employee training, and proposing program such as cash discount or bonus product to maintain customer retention.